2021
DOI: 10.1155/2021/6688346
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio as a Prognostic Parameter in NSCLC Patients Receiving EGFR-TKIs: A Systematic Review and Meta-Analysis

Abstract: Objective. To research the impact of neutrophil-lymphocyte ratio (NLR) as a prognostic parameter in non-small-cell lung cancer (NSCLC) patients treated with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). Methods. We searched the databases such as the American Society of Clinical Oncology (ASCO), EMBASE, PubMed, the European Society of Medical Oncology (ESMO), Wanfang, and CNKI for articles illustrating the impact of pretreatment NLR on survival data in NSCLC patients undergoing EGFR-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Prior studies have looked solely at pretreatment NLR and have found that pretreatment NLR is an independent predictor of PFS and OS [9,32]. We did not observe NLR at the pretreatment stage (i.e., time of therapy initiation) to be an independent predictive factor as prior studies have reported, possibly due to our limited sample size and the strong association between baseline number of disease sites with OS and PFS, and ECOG score with OS and PFS.…”
Section: Discussioncontrasting
confidence: 69%
“…Prior studies have looked solely at pretreatment NLR and have found that pretreatment NLR is an independent predictor of PFS and OS [9,32]. We did not observe NLR at the pretreatment stage (i.e., time of therapy initiation) to be an independent predictive factor as prior studies have reported, possibly due to our limited sample size and the strong association between baseline number of disease sites with OS and PFS, and ECOG score with OS and PFS.…”
Section: Discussioncontrasting
confidence: 69%
“…Decreased lymphocyte values are associated with decreased ability to eradicate tumors. TILs are components of TME that regulate the inflammatory response and have an important role in the eradication of tumor cells [23,24]. This study showed that there was no difference in PFS in the exon 19 mutation group and the exon 21 mutation group (12.00 (9.76-14.23) versus 12.00 (10.18-13.81), p = 0.499).…”
Section: Discussionmentioning
confidence: 69%
“…This meta-analysis used 10 studies with different NLR cut-offs. Patients with low NLR had better PFS (HR 1.67, 95% CI 1.16-2.39, p=0.005) [23]. A study by Phan et al in Vietnam also demonstrated NLR as a prognostic factor for poor PFS.…”
Section: Discussionmentioning
confidence: 92%
“…e prognostic value of NLR has been proven in various types of cancer [26][27][28][29]. Bagley [26] and Soyano [27] argued that high NLR was significantly associated with poor OS and PFS in NSCLC patients receiving ICIs.…”
Section: Discussionmentioning
confidence: 99%